(untitled) (Journal of Economic Research & Business Administration, 2017)
The article discusses the development of new types of lending, both in cash and in the form of commodities, in particular the leasing activity, becoming an important lever for the activation of innovative activity in the enterprises and the expansion of business in the modern conditions. The particular importance of leasing was highlighted as investment tool, acquiring an significant role in the conditions of economy transformation and modernization of material-technical base in the production. It is shown, that the use of leasing relations activates the investment of private capital in the production sphere, improve the financial condition of the producers and increase the competitiveness of small and medium-sized businesses, whose work is an additional resource for the development of the complex in the country and its regions.